Design Research of Mathematical Problem Solving Ability in Era 4.0: Pengaruh Model Pembelajaran SOLE and Self-Regulated Learning - Risqa JL, Ana; Rahmita, Nela; Alhaq, Arini; Dewi, Novian Riskiana (Indo-MathEdu Intellectuals Journal, 2025)
The ability to solve mathematical problems can be interpreted as a potential possessed by students so that they can solve mathematical problems in solving mathematical problems. This quantitative research explains the mathematical problem-solving ability of students by implementing the SOLE (Self Organized Learning Environments) learning model and self-regulated learning of students as a controller. This study aims to determine the effect of the SOLE learning model on students' mathematical problem solving abilities by controlling self-regulated learning and the effect of self-regulated learning covariate variables on students' mathematical problem solving abilities, as well as the simultaneous effect of the SOLE learning model and self-regulated learning on students' mathematical problem solving abilities. Participants in this study totaled 61 students in junior high school, with details of 30 students studying using the SOLE model and 31 students studying with the conventional model. The tools used to collect data are questionnaires and essay tests. The hypothesis test uses the one-way ancova test, the result of the hypothesis test is that there is an influence of the SOLE learning model on students' mathematical problem-solving ability by controlling self-regulated learning and there is an influence of self-regulated learning covariate variables on students' mathematical problem-solving ability, and there is a simultaneous influence of the SOLE learning model and self-regulated learning on mathematical problem-solving ability.